Aristaless controls butterfly wing color variation used in mimicry and mate choice - Westerman, Erica (Curr Biol, 2018)
Westerman, VanKuren et al. show that butterfly wing color maps to a putative cis-regulatory element adjacent to two aristaless genes. The genes are differentially expressed between white and yellow wings and CRISPR knockout of aristaless1 causes white wings to develop yellow. Both colors have been shared among species via hybridization.